c= (a,b)+(b,c)-(a,b)*(c,b);
if a,b,c are respectively 1,2,3
c= (a,b)+(b,c)-(a,b)*(c,b);
if a,b,c are respectively 1,2,3
What is the comma suppose to do here? Is this a algebraic expression?
If so you could just do:
c= (a*b)+(b*c)-(a*b)*(c*b);
Yes this is an algebric expression if it was like (a*b) i know how to solve that
but dunno how to solve expressions involvins commas
I dont think I really understand your question
3 = (1,2) + (2,3) - (1,2) * (3,2) ?
are you asking how to solve this problem in general or in c?
-- Will you show me how to c++?
the complete problem is like this
and its answer is 6Code:void main() { int a=1,b=2,c=3,d=4,e; e=(a,a)+(b,c)+(c,d)-(d,b); printf("%d",e); }
compiler is giving the output but i just want to know how it is being interpreted by compiler
hope u understand my program now
That doesn't make a whole lot of sense to do, but out of the ordered pairs, only the second value will impact the result.